Knowledge Management to Support Performance-based Medicine - Stefanelli, M. (Methods of Information in Medicine, 2002)
Objectives: To discuss research issues for medical informatics in order to support the further development of health information systems, exploiting knowledge management and information and communication technology to increase the performance of Health Care Organizations (HCOs).Methods: Analyze the potential of exploiting knowledge management technology in medicine.Results and conclusions: The increasing pressure on HCOs to ensure efficiency and cost-effectiveness, balance the quality of care, and contain costs will drive them towards more effective management of medical knowledge derived from biomedical research. Knowledge management technology may provide effective methods and tools in speeding up the diffusion of innovative medical procedures. Reviews of the effectiveness of various methods of best practice dissemination show that the greatest impact is achieved when such knowledge is made accessible through the health information system at the moment it is required by care providers at their work sites. There is a need to take a more clinical process view of health care delivery and to identify the appropriate organizational and information infrastructures to support medical work. Thus, the great challenge for medical informatics is represented by the effective exploitation of the astonishing capabilities of new technologies to assure the conditions of knowledge management and organizational learning within HCOs.
Keywords: Health care organization; evidence based medicine; patient care process; knowledge management; careflow management